Treaty - Brennan, Sean, 1965- (Annandale, N.S.W. : Federation Press, 2005)
Australia's first peoples are on the lowest rung of our society and are largely locked out of the wealth of a very affluent country. This book takes a practical look at whether modern treaty making between Indigenous peoples and government in Australia is feasible and whether a treaty could help solve these problems.
Includes index.
Keywords: Aboriginal Australians -- Treaties; Aboriginal Australians -- Land tenure; Aboriginal Australians -- Civil rights; Social justice -- Australia; Race relations - Reconciliation; Colonisation; Law - Constitutional law - Constitutional reform; Law - Constitutional law - Treaty movement; Native title; Politics and Government - Sovereignty; Australia -- Race relations -- Political aspects; New Zealand (NZ); United States (USA); Australia; Canada